Waterborne polyurethane and graphene/graphene oxide-based nanocomposites: Reinforcement and electrical conductivity - I. Larraza; B. Alonso-Lerma; K. Gonzalez; N. Gabilondo; R. Perez-Jimenez; M. A. Corcuera; A. Arbelaiz; A. Eceiza (eXPRESS Polymer Letters, 2020)
Polyurethane based materials show great potential for many applications, and their reinforcement with different kinds of nano-entities can improve their properties or supply them with new ones, widening their fields of applications to new opportunities. In this work, nanocomposites composed of a biobased waterborne polyurethane and carbonaceous reinforcements were prepared and characterized. Parting from graphite, graphene, and graphene oxide were obtained through a mechanical and a chemical route, respectively, and graphene oxide was reduced into graphene through a thermal process. Successful exfoliation, oxidation, and reduction processes were proven when characterizing graphene, graphene oxide, and reduced graphene oxide. Nancomposites reinforced with graphene and graphene oxide showed improved mechanical and thermomechanical properties, whereas they did not show electrical conductivity. Coatings of the systems with graphene and reduced graphene oxide were studied, to grant electrical properties to the composites. Electrical conductor materials were obtained after coating the systems, as shown by Electrostatic Force Microscopy and electrical conductivity measurements.